Co-infection of Chlamydia psittaci with H9N2, ORT and Aspergillus fumigatus contributes to severe pneumonia and high mortality in SPF chickens. Issue 1 (December 2017) - Chu, Jun; Zhang, Qiang; Zuo, Zonghui; El-Ashram, Saeed; Guo, Yongxia; Zhao, Peng; Huang, Shujian; He, Cheng; Khan, Ahrar
Abstract Since 2007, most areas of China have seen outbreaks of poultry airsacculitis, which causes hugely economic losses to the poultry industry. However, there are no effective measures to combat the problem. In this study, 105 rations were collected to isolateAspergillus spp. from the diseased farms. In subsequent experiments, SPF chickens were inoculated withOrnithobacterium rhinotracheale (ORT), Chlamydia psittaci (C. psittaci ) andAspergillus fumigatus (A. fumigatus ), and mortality rate, body weight gain and lesion score were evaluated. Of these ration samples, 63 (60.0%) wereA. fumigates, 21 (20.0%) wereAspergillus niger (A. niger ) and 11 (10.5%) wereAspergillus candidus (A. candidus ). Furthermore, SPF birds infected withC. psittaci, ORT, H9N2 virus andA. fumigatus conidia exhibited a mortality rate of 40%, while simultaneous co-infection withC. psittaci, ORT andA. fumigatus resulted in a mortality rate of 20%. The avian airsacculitis was manifested in theC .psittaci + ORT/A. fumigatus, C. psittaci + H9N2 + ORT/A. fumigatus andC. psittaci + H9N2/A. fumigatus groups while others had transient respiratory diseases without mortality. Our survey indicates that feed-borneA. fumigatus is prevalent in poultry rations. The combination ofC. psittaci, ORT, H9N2 andA. fumigatus conidia contributes to the replication of avian airsacculitis by aggravating the severe damage to the air sacs and lungs of chickens.